Characteristics of vital features of strawberry plants by long-term covering with non-woven material - O. N. Budagovskaya; I. I. Kozlova (Аграрная наука Евро-Северо-Востока)
The vital features of Elsanta and Vima Xima strawberry varieties by long-term covering with white and yellow "Spunbond" fabric of 17 g/m2 density in the moderate continental climate of the Central Black Earth Region of the Russian Federation were studied. In 2015-2016 during the process of vegetation light intensity. soil and air temperature as well as dry weight. leaf area. maximum Fm and stationary FT fluorescence level. photosynthetic activity index Y = (Fm - FT)/Fm were determined. Both varieties are characterized by a decrease in the Y parameter of strawberry leaves by 16-22% under white material. especially during active vegetation (July - first decade of August). which is less evident under yellow fabric (3-9 %). It is shown that such a reaction is due to the optical properties of the cover. as the yellow material transmission index is 7.2% higher in the red region of the spectrum and 13.8% lower in the blue region of the spectrum as compared to white fabric. By the development of new agricultural technologies and correct interpretation of the received results with the use of non-woven polypropylene cover material "Spunbond". especially for long-term operation. it is necessary to control and take into account not only the shielding but also the spectral characteristics of the material.